Macromedia dreamweaver MX 2004 demystified. - Gutman, Laura, ....- (Berkeley : Macromedia, 2004)
As an experienced Dreamweaver developer, you don't need a guide to step you through every new Dreamweaver MX 2004 button and feature. Chances are, you'll be able to figure most of those out on your own. What you need--and this volume delivers--is an in-depth exploration of how you can leverage all of Dreamweaver's power to take your own Web development process to the next level. Moving beyond the explanations that are readily available in the product's documentation and the commonly available introductory guides, author Laura Gutman draws on her own extensive experience as a multimedia Web application developer to explore some of the software's more creative and complex uses--many of which involve features new to Dreamweaver MX 2004: editing files, manipulating databases, and changing code directly on remote FTP and network servers without first stetting up a Dreamweaver site; using CSS to improve your design procedures; and more. Easy-to-follow explanations, insightful exercises, render a complex topic painless.
Keywords: Elektronisch publiceren; Programmatuurontwikkeling; Www world wide web